PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT SC JOHNSON AND SON - Sesilia Novita Sari; Iwan Kurniawan Subagja (Jurnal Ekonomi dan Industri, 2023)
This research aims to test and determine the influence of organizational culture and competency on employee performance simultaneously and partially. Research was conducted on employees of PT. SC Johnson and Son Indonesia. The sampling technique used simple random sampling and data analysis used multiple and simple linear regression analysis. The results of the research showed that organizational culture and competency had a positive and significant effect both simultaneously and partially on employee performance.